Phytochemical Screening and Hypoglycemic Activity of Aqueous, Ethanolic and Methanolic Extracts of Phyllanthus Amarus and Catharanthus Roseus in Streptozotocin Induced Diabetic Rats: Evaluation of the Hypoglycemic Activity of Phyllanthus Amarus and Catharanthus Roseus Extracts in Streptozotocin-Induced Diabetic Rats (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The aim of the present study was to evaluate the hypoglycemic activity of Gymnema sylvestre and Phyllanthus amarus leaf extract in streptozotocin induced diabetic rats. Diabetes mellitus was induced by a single intraperitoneal injection of STZ (50 mgkg body weight). The experimental set up was formed as follows Group I–Normal Rats injected with normal saline is considered as vehicle control, Group II–Diabetic control administered with 20 Glucose Soln. for 14 days, Group III–STZ induced diabetic Wistar rats, administered with standard drug (Glibenclamide) 5 mgkg for 14 days, served as positive control, GROUPS-IV to IX STZ induced diabetic Wistar rats were orally administered with Aqueous, ethanolic and methanolic extracts of Phyllanthus amarus and Catharanthus roseus, at the dose of 300 mgkg rat body weight respectively. The results of the study indicates that Phyllanthus amarus and Catharanthus roseus extract significantly (P